Antibiotic treatment during early childhood and risk of type 1 diabetes in children: A national birth cohort study. Issue 8 (1st October 2020) - Antvorskov, Julie Christine; Morgen, Camilla Schmidt; Buschard, Karsten; Jess, Tine; Allin, Kristine Højgaard; Josefsen, Knud
Abstract: Objective/Background: Antibiotics are widely used during childhood infections and influence the composition of the microbiota, which is established during the first years of life. Evidence from animal models of type 1 diabetes shows that antibiotics might accelerate disease progression, and altered intestinal microbiota has been reported in association with type 1 diabetes in humans. We aimed to test the hypothesis that early exposure to antibiotics (0‐24 months of age) was associated with an increased risk of childhood type 1 diabetes development. Methods: We studied 75 615 mother‐child dyads from the Danish National Birth Cohort. Information on the use of antibiotics during early childhood and type 1 diabetes development in childhood was available for all children via linkage to the Danish National Prescription Registry and the Danish National Patient Register, respectively. The mean follow‐up time was 14.3 years (range 11.5 to 18.4 years, SD 1.4). Results: After adjustment for confounders, we found no association between antibiotic exposure and risk of type 1 diabetes (HR 1.26, 95% CI 0.89‐1.79). The number of antibiotic courses during early childhood was not associated with type 1 diabetes development when analyzing for one (HR 1.31, 95% CI 0.87‐1.99), two (HR 0.99, 95% CI 0.61‐1.63), or 3 or more (HR 1.42, 95% CI 0.95‐2.11) courses. Furthermore, no specific types of antibiotics (penicillins/beta‐lactam antibacterials, sulfonamide/trimethroprim, or macrolides/lincosamides/streptogramins) were associated with increased risk of type 1 diabetes. Conclusion: Our nationwide cohort study suggests that postnatal exposure to antibiotics does not influence the development of childhood type 1 diabetes.